386 A Count of three Neonatal Morbidities may Substitute for Long-Term Neurodevelopmental follow-up in very Low Birth Weight (VLBW) Infants. (October 2012) - Schmidt, B; Roberts, R; Davis, P; Doyle, L; Asztalos, E; Opie, G; Bairam, A; Solimano, A; Arnon, S; Sauve, R
Abstract : Background: In very preterm infants who survive to a postmenstrual age (PMA) of 36 weeks, a count of BPD, brain injury and severe ROP predicts the risk of a later death or neurosensory impairment at 18 months (JAMA 2003; 289:1124). Objective: To validate this count of 3 neonatal morbidities as a predictor of poor long-term outcome in VLBW infants who participated in the CAP Trial. Methods: Five-year follow-up of 1514 CAP trial participants who survived to a PMA of 36 weeks. Poor outcome was a late death or survival with one or more disabilities. Results: The incidences of BPD, brain injury and severe ROP were 40%, 13%, and 6.0%, respectively. Each morbidity was similarly and independently correlated with a poor 5-year outcome. Table 1 shows the risks of a poor long-term outcome with none, any 1, any 2, and all 3 neonatal morbidities. Conclusions: In VLBW infants who survive to a PMA of 36 weeks, a count of BPD, brain injury and severe ROP predicts the risk of a later death or survival with disability at age 5 years. This morbidity count may substitute for long-term outcome assessments in very preterm infants whose families do not comply with neurodevelopmental follow up.